The Portrait of Challenges in Teaching English to Young Learners: A Case Study in an Indonesian Islamic School - Canda Ayu Arum Pertiwi; Mutmainnah Mustofa; M Faruq Ubaidillah; Sugeng Hariyanto (Yayasan Visi Intan Permata, 2022)
Teaching English to students with no prior knowledge, a different first language, and varied characters is challenging. This research is a case study design that focused on the teachers’ perceptions of teaching English to young learners situated in one of the Islamic schools in Malang, Indonesia. The participants involved were six English teachers at the chosen school. A qualitative approach was employed in this study. Data were generated through interviews. Findings suggest that the participating teachers encountered multiple challenges in their teaching enactment, such as (1) non-English prior knowledge, (2) lack of motivation, (3) negative perceptions of the English language, (4) time constraints for studying English, (5) insufficient teaching and learning devices, (6) messy classroom conditions, and (7) speaking anxiety. With some help from others, teachers’ creativity, and some collaborations with other teachers, the teaching and learning process can run conditionally.